Chemistry and Physics of Wet Foam Stability for Porous Ceramics: A Review - Kamrun Nahar Fatema; Md Rokon Ud Dowla Biswas; Jung Gyu Park; Ik Jin Kim (Micro)
The unique structural properties of porous ceramics, such as low thermal conductivity, high surface area, controlled permeability, and low density, make this material valuable for a wide range of applications. Its uses include insulation, catalyst carriers, filters, bio-scaffolds for tissue engineering, and composite manufacturing. However, existing processing methods for porous ceramics, namely replica techniques and sacrificial templates, are complex, release harmful gases, have limited microstructure control, and are expensive. In contrast, the direct foaming method offers a simple and cost-effective approach. By modifying the surface chemistry of ceramic particles in a colloidal suspension, the hydrophilic particles are transformed into hydrophobic ones using surfactants. This method produces porous ceramics with interconnected pores, creating a hierarchical structure that is suitable for applications like nano-filters. This review emphasizes the importance of interconnected porosity in developing advanced ceramic materials with tailored properties for various applications. Interconnected pores play a vital role in facilitating mass transport, improving mechanical properties, and enabling fluid or gas infiltration. This level of porosity control allows for the customization of ceramic materials for specific purposes, including filtration, catalysis, energy storage, and biomaterials.